Clinical characteristics and survival outcomes in patients aged 75 years or older with advanced colorectal cancer treated using traditional Chinese medicine: an observational retrospective study - Wu, Jiao; Cui, Ning; Li, Zhongyu; Wu, Yu; Hao, Tengteng; Li, Liusheng (Frontiers in Pharmacology, 2023)
Limited evidence suggests that elderly patients with advanced colorectal cancer (ACRC) may benefit from traditional Chinese medicine (TCM). This study investigated the efficacy and safety of TCM in old ACRC patients treated in the Oncology Department of Xiyuan Hospital between January 2012 and December 2021. The clinical characteristics of these patients were retrospectively reviewed. Their progression-free survival (PFS) and total duration of TCM therapy (TTCM) were analyzed using the Kaplan-Meier curve. Forty-eight patients (F:M 13:35) with a mean age of 78.75 ± 2.99 years (range, 75–87) met the inclusion criteria. There were 18 cases of rectal cancer and 30 of colon cancer. The median PFS was 4 months (range, 1–26; 95% CI 3.26–4.73). The median TTCM was 5.5 months (range, 1–50; 95% CI 1.76–8.24). Subgroup analysis revealed that PFS and TTCM were shorter in patients with bone metastases and an ECOG performance status score of 2–3 (p < 0.05). No hematological toxicity or serious adverse reactions occurred during the study period. This real-world study demonstrates that TCM may be a potentially beneficial therapy for old ACRC patients, including when the ECOG performance status score is 2–3.